Mohandas Gandhi - Downing, David, 1946- (2002)
A biography of Mahatma Gandhi, the Indian political and spiritual leader who led his country to freedom from British rule through his policy of nonviolent resistance.
Includes bibliographical references (page 60) and index.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Juvenile literature; Nationalists -- India -- Biography -- Juvenile literature; Statesmen -- India -- Biography -- Juvenile literature; India -- Politics and government -- 1919-1947 -- Juvenile literature